The impacts of intensive mining on terrestrial and aquatic ecosystems: A case of sediment pollution and calcium decline in cool temperate Tasmania, Australia. (October 2020) - Beck, K.K.; Mariani, M.; Fletcher, M.-S.; Schneider, L.; Aquino-López, M.A.; Gadd, P.S.; Heijnis, H.; Saunders, K.M.; Zawadzki, A.
Abstract: Mining causes extensive damage to aquatic ecosystems via acidification, heavy metal pollution, sediment loading, and Ca decline. Yet little is known about the effects of mining on freshwater systems in the Southern Hemisphere. A case in point is the region of western Tasmania, Australia, an area extensively mined in the 19th century, resulting in severe environmental contamination. In order to assess the impacts of mining on aquatic ecosystems in this region, we present a multiproxy investigation of the lacustrine sediments from Owen Tarn, Tasmania. This study includes a combination of radiometric dating ( 14 C and 210 Pb), sediment geochemistry (XRF and ICP-MS), pollen, charcoal and diatoms. Generalised additive mixed models were used to test if changes in the aquatic ecosystem can be explained by other covariates. Results from this record found four key impact phases: (1) Pre-mining, (2) Early mining, (3) Intense mining, and (4) Post-mining. Before mining, low heavy metal concentrations, slow sedimentation, low fire activity, and high biomass indicate pre-impact conditions. The aquatic environment at this time was oligotrophic and dystrophic with sufficient light availability, typical of western Tasmanian lakes during the Holocene. Prosperous mining resulted in increased burning, a decrease in landscape biomass and an increase in sedimentation resulting in decreased light availability of the aquatic environment. Extensive mining at Mount Lyell in the 1930s resulted in peak heavy metal pollutants (Pb, Cu and Co) and a further increase in inorganic inputs resulted in a disturbed low light lake environment (dominated by Hantzschia amphioxys and Pinnularia divergentissima ). Following the closure of the Mount Lyell Co. in 1994 CE, Ca declined to below pre-mining levels resulting in a new diatom assemblage and deformed diatom valves. Therefore, the Owen Tarn record demonstrates severe sediment pollution and continued impacts of mining long after mining has stopped at Mt. Lyell Mining Co. Graphical abstract: Image 1 Highlights: Mining has caused extensive environmental degradation in Tasmania. A palaeoenvironmental study investigated the impacts of mining on an aquatic ecosystem. The Owen Tarn record revealed four key impact phases. Pre-mining, Early mining, Intense mining, and Post mining impacts. Owen Tarn is impacted by severe sediment pollution and Ca decline from mining. Abstract : The Owen Tarn record revealed four impact phases: Pre-mining, Early mining, Intense mining, and Post mining. Mining caused severe sediment pollution and Ca decline in the aquatic environment.